2021
DOI: 10.1002/ece3.7234
|View full text |Cite
|
Sign up to set email alerts
|

Environmental conditions but not nest composition affect reproductive success in an urban bird

Abstract: Environmental conditions during development are critical for survival and can affect the expression of behavioral and life-history traits (Lindström, 1999;Metcalfe & Monaghan, 2001). Changes in external conditions are particularly relevant for oviparous species (e.g., reptiles and birds). In these species, embryos develop inside an egg and are potentially exposed to environmental shifts that can involve suboptimal conditions for development (Ackerman & Lott, 2004;Ar & Sidis, 2002). In order to reduce such envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 41 publications
(86 reference statements)
1
5
0
Order By: Relevance
“…This is likely to be the case in our field sites too where invertebrates are subject to the same weather limitations. Our findings on precipitation are also supported by Capilla‐Lasheras et al (2021) who found that high precipitation in the first 10 days of nestling development correlated with less nestlings successfully fledging. That study uses precipitation averages from the first 10 days of nestling development whilst our study is more specific, giving exact days when this is most important.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…This is likely to be the case in our field sites too where invertebrates are subject to the same weather limitations. Our findings on precipitation are also supported by Capilla‐Lasheras et al (2021) who found that high precipitation in the first 10 days of nestling development correlated with less nestlings successfully fledging. That study uses precipitation averages from the first 10 days of nestling development whilst our study is more specific, giving exact days when this is most important.…”
Section: Discussionsupporting
confidence: 90%
“…Unless climate breakdown comes to a halt, nestling haematocrit will likely become sub‐optimum in both locations and as a result nestling fitness will suffer. This may also impact post‐fledging survival rates and longevity in the future as has been observed in other passerines (Facey et al 2020, Brown et al 2021, Capilla‐Lasheras et al 2021).…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Artificially heating Tree Swallow nests also had no effect on the number of feathers added to the nest during building or the reproductive outcome of the clutch (Holland & Shutler 2018). Capilla-Lasheras et al (2021) also concluded that the numbers of feathers in Tree Sparrow Passer montanus nests did not have an importance in protecting eggs or nestlings against fluctuations in environmental conditions.…”
Section: Factors Affecting Thermal Properties Of Nestsmentioning
confidence: 99%